(untitled) (EAAE Joint Publishings, 2026)
Unique microclimates in urban plazas around tall buildings impact people’s presence, which is driven by the Outdoor Thermal Comfort (OTC) levels. Increasing interest in OTC studies due to their significant contribution to the UN Sustainable Development Goal SDG11 has led to the development of advanced OTC indices. Urban designers and planners strive to gain knowledge in assessing their outdoor public space designs through these indices, thus understanding the impact of such developments on people’s social lives. Microclimate CFD simulation is a popular method commonly employed on this topic. This study uses CFD simulation using ENVImet to model microclimates and OTC indices for five urban plazas in downtown Chicago with Dfa climate zone. The study adopts a spatiotemporal approach to assess three OTC indices, namely, Physiological Equivalent Temperature (PET), Standard Effective Temperature (SET*), and Universal Temperature Climate Index (UTCI). Using physiological thermal stress levels as a basis for comparison, the spatial approach involves the distribution of comfort regimes in the plazas, while the temporal approach uses the mean values of the OTC indices to address the research objectives, which are (a) comparing ‘neutral’ comfort regimes of PET, SET*, & UTCI during a peak lunch hour of the summer solstice day, (b) exploring spatial distribution of neutral regimes of these indices, (c) temporal analysis of PET thermal stress categories and microclimatic variables between 12-2 pm, and (d) spatiotemporal analysis of the same within and between the plazas. The findings show that SET* and UTCI lack granularity around neutral thermal stress regimes, unlike PET, which limits the understanding of finer thermal conditions that may exist in the plazas and could be critical in the success of the plaza. The other key findings of this study highlight the importance of the spatial distribution of thermal stresses in assessing the thermal conditions of an outdoor environment.